Thinking About a Word—Love, for Example. (January 2017) - Forsberg, Niklas
Abstract: What is it we do when we philosophize about a word? How are we to act as we ask the philosophical question par excellence, "What is … ?" These questions are addressed here with particular focus on Troy Jollimore's Love's Vision and contemporary theories of love. Jollimore's rationalist account of love, based on a specific understanding of "reasons for love, " illustrates a particular philosophical mistake: When we think about a word, we are prone to believe that even though "the sense of the word" that we investigate may be up for grabs, the other words we use when we do these investigations are not. Jollimore's exploration of love is guided by specific conceptions of "reasons" and "rationality" that remain unquestioned. The article argues that we may have to rethink a great number of words as we embark on the task of uncovering the sense of one word.